Construction of Greenhouse for Horticultural Cultivation with Soil Media and Hydroponics: Pembangunan Greenhouse untuk Budidaya Hortikultura dengan Media Tanah dan Hidroponik (Indonesian Journal of Cultural and Community Development, 2024)
Theneral background greenhouse technology is increasingly recognized as an efficient solution for sustainable agricultural practices, especially in regions with limited fertile land. Specific background In Kedungpeluk Village, where the majority of residents work as fish farmers, there are also unused and arid lands. These underutilized spaces provide an opportunity for greenhouse-based horticultural cultivation using soil media and hydroponic technology. Knowledge gap however, limited knowledge and infrastructure have prevented local farmers from effectively utilizing these lands for sustainable crop production. Aims this community engagement project aims to build and utilize a greenhouse system to cultivate horticultural plants, focusing on optimizing both soil and hydroponic methods. Results the project successfully transformed barren land into productive greenhouses that facilitate the growth of tomatoes, chilies, eggplants, pak choy, and water spinach. The greenhouse structure, designed with transparent roofing, enhances sunlight exposure, promoting optimal plant growth. Both soil and hydroponic methods showed potential for increasing crop yields, with soil cultivation being more flexible but requiring extra care for pests, while hydroponics provided faster results with minimal weed and pest interference. Novelty this project introduces a dual-method approach combining traditional soil cultivation with modern hydroponic technology in a controlled greenhouse environment. Implications the findings highlight that greenhouse farming is a viable, modern agricultural solution for rural communities, offering increased productivity and quality crops, while also addressing the challenges of limited fertile land and changing climate conditions. This project serves as a model for sustainable agriculture in similar settings.Highlights: • Dual-method approach: Combining soil and hydroponic techniques in a greenhouse.• Efficient land use: Transforming unused arid land for productive horticulture.• Controlled environment: Optimizing plant growth through sunlight, temperature, and humidity control.Keywords: Greenhouse, Horticulture, Soil Media, Hydroponics, Sustainable Agriculture